(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective: To assess physical and psychological stress for nurses during day and rotating shift work. To find out the relationship job satisfaction and demographic data and Finally to find out the relationship between physical and psychological stress for nurses and demographic data.Methodology: A Descriptive study design (correlation study) was carried out through the present study in order to achieve the early stated objectives. From period 15th of May 2021 to 20th of June 2021 A non-probability (purposive sample) of (137) nurses who were works in governmental hospitals were included in the study. The data were collected through the utilization of the developed questionnaire, consist of two parts: part I consists of demographic data contain (6) items, and part II include the Standard Shift Work Index Scale (SSI) which consist of three subsection as “Work situation, General job satisfaction and psychosomatic symptoms.Results: The result of present study indicate that highest percentage of the nurses' are females (54%) within age group (≥ 25) years old (56.2%), who are married (66.4 %), and graduated from nursing colleges (63.5 %) and lives in urban residential area (82.5%), and those with monthly income which sufficient to meet some extent (38.7 %), Furthermore, the overall assessment for job satisfaction is partially satisfied while psychosomatic stress among nurses is (moderate). Conclusion: The study concludes that more than half of nurses are partially satisfied about your job due to most them are suffering from psychosomatic stress so the study find that there is a high significant correlation between psychosomatic stress and job satisfaction (r= 0.441) at (P<0.01).